Social enterprises\' dilemma: navigating tensions through and because of stakeholder engagement - Barros, Filippe Delarissa (2025)
Although there are studies on how social enterprises handle their tensions, there is a gap in the literature on how these ventures can overcome tensions through stakeholder engagement. Because of this, this study has the following research question: How and why is stakeholder engagement associated with tensions in social enterprises? Thus, the goal is to understand the relationship between stakeholder engagement and tensions in social enterprises. A single-case study was conducted, following a constructivist epistemology. The selected case was Central da Visão, and data collection included secondary data, mystery shopping, and 17 in-depth interviews with shareholders, employees, physicians, investors, and clients. Through content analysis, twenty first-order categories were identified, which were grouped into eight second-order categories and three aggregate dimensions. As a result, the study presents the enterprises tensions from the stakeholders perspective, classifying them as How to Grow and How to Manage Tensions. The study also identifies the stakeholder engagement activities carried out by the enterprise, their aims, and their mechanisms. Finally, the research highlights that before social enterprises use stakeholder engagement to mitigate tensions, they must first define the boundaries between expected social impact and financial results, as well as identify stakeholders whose values align with the enterprises values. The study also shows that stakeholder engagement can mitigate tensions as either a means or an end, but may also create tensions due to misaligned expectations or the necessary investment in engagement activities with marginalized stakeholders. This study contributes to the literature by developing eight propositions and a theoretical model on the relationship between stakeholder engagement and tensions. It also offers managerial contributions by informing decision-making for social enterprise managers and their stakeholders, potentially strengthening partnerships and support for these ventures. Lastly, the study provides a social contribution by potentially encouraging government actions to foster social entrepreneurship, which is crucial for achieving the Sustainable Development Goals.